Vitamin E in the treatment of viral hepatitis - Yurdakök, Murat; Kanra, Güler (The Turkish Journal of Pediatrics, 1985)
Vitamin E therapy was compared with no treatment in a randomized, prospective trial of treatment of viral hepatitis in children. Patients received either vitamin E (n: 21) 300 mg/day intramuscularly every 24 hours, for seven days, or no treatment (n: 20). The mean age, sex ratio, and mean duration of illness before admission to the study of the two groups were similar. No difference was noted in the mean serum transaminases or alkaline phosphatase levels either on the first or the eighth day in the treatment group compared to the group without treatment.